Studying regenerated soybean lines for their useful agronomic and biochemical characteristics - E. S. Butovets; l. M. lukyanchuk; G. A. Kodirova; G. V. Kubankova; O. S. Efremova (Труды по прикладной ботанике, генетике и селекции)
Background. The effect of heavy metal ions can cause ionic stress in plants – the problem of significant interest among researchers. This study was dedicated to the evaluation of genetically modified regenerated soybean lines obtained on nutrient media with heavy metal ions as a mutagenic factor.   Materials and methods. Genetically modified regenerated soybean lines were tested at the Agricultural Biotechnology Laboratory and Soybean Breeding Laboratory, Federal Scientific Center of Agricultural Biotechnology of the Far East named after A. K. Chaika, and at the Agricultural Product Processing Laboratory, All-Russian Research Institute of Soybean.   Object of the study. Fifteen regenerated soybean lines and source cultivars (‘Primorskaya 13’, ‘Primorskaya 301’, ‘Primorskaya 81’, and ‘Hodson’) served as the research material.   Results. Soybean accessions promising for further breeding were selected on the basis of their useful agronomic traits, grain quality, and resistance to fungal diseases. Accessions R 1490 (0.41 kg/m2) and R 1606 (0.38 kg/m2) were identified for having the highest yield in the experiment. Accessions R 1568 (1000 seed weight was 200.0 g) and R 1609 (190.2 g) had the largest seeds. Accessions R 1584, R 1568 and R 1606 manifested complex resistance to fungal diseases under natural conditions, while accession R 1490 was the most resistant under artificial infection pressure. The experiment resulted in selecting a group of lines regenerated from cv. ‘Hodson’ with high content of protein, histidine, valine, methionine, and cysteine. Accessions R 1605 and R 1609 demonstrated the highest oil content. The study revealed changes in the proportions of unsaturated fatty acids С18:2/С18:1 in all regenerant groups.